PROFIL KESEHATAN CALON PENGANTIN WANITA DI KANTOR URUSAN AGAMA KALIWATES JEMBER : Health profile of future bride in religious Affairs office - Ernawati Anggraeni Erna (LPPM - STIKES Pemkab Jombang, 2022)
The Premarital Check-up Program is one of the programs designed by the government to improve the quality of human resources for newborns, examination is used as a preventive, more precisely in premarital or before marriage in the hope of preparing for a healthy pregnancy in an effort to reduce AKI and AKB. The purpose of this activity is premarital check-up screening for prospective brides. This study uses direct observation and examination of prospective brides. The examinations carried out include physical examination of height, weight, LILA, blood pressure, laboratory examination of hemoglobin levels, glucose levels. The population in this study is the bride. The results of direct examination of the prospective bride, there are still prospective brides whose nutritional status is calculated from the count BMI is still in the poor category (21.3%) and LILA status is still in the poor category (17%), so education is needed about premarital check-up and preparation for being a healthy mother.